2019
DOI: 10.3847/1538-4357/ab1a34
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of a Coma-analog Protocluster at z = 6.5

Abstract: We present evidence for the discovery of a protocluster of starburst galaxies (Lyα emitters, or LAEs) near the end of the epoch of reionization. The recent trend in the search for high-redshift protoclusters focuses on utilizing bias tracers, such as luminous starburst galaxies, as signposts of overdensities. Thus, we conducted a photometric selection of LAE candidates around a pair of spatially close, luminous LAEs at z=6.5 in the Subaru/XMM-Newton Deep Survey field, using OSIRIS in its imaging mode at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 91 publications
5
25
0
Order By: Relevance
“…In particular, we have shown that the sources discussed in this paper belong to a proto-cluster (Chanchaiworawit et al 2019). In Chanchaiworawit et al (2019) we have discussed 1) the presence of a virialised core, and 2) the evolution of the whole proto-cluster, which will virialise by z∼ 0.84, and by z= 0 will reach a mass comparable to that of the Coma cluster (Chanchaiworawit et al 2019). The size of the protocluster, encompassing these sources, is 10873 ± 1679 cMpc 3 .…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…In particular, we have shown that the sources discussed in this paper belong to a proto-cluster (Chanchaiworawit et al 2019). In Chanchaiworawit et al (2019) we have discussed 1) the presence of a virialised core, and 2) the evolution of the whole proto-cluster, which will virialise by z∼ 0.84, and by z= 0 will reach a mass comparable to that of the Coma cluster (Chanchaiworawit et al 2019). The size of the protocluster, encompassing these sources, is 10873 ± 1679 cMpc 3 .…”
Section: Introductionmentioning
confidence: 74%
“…This paper (Paper II) deals with the follow-up multi-object spectroscopy of a subset of the LAE candidates reported in Paper I. A third paper (Chanchaiworawit et al 2019), discusses the clustering properties of these LAEs, the mass of the overdensity, and its growth via linear spherical collapse. In particular, we have shown that the sources discussed in this paper belong to a proto-cluster (Chanchaiworawit et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median protocluster in the compilation has a present-day mass of log(M (z = 0)/M ⊙ )=14.6. This makes our protocluster one of the most massive systems with a z=0 mass comparable to some remarkable high-z protoclus-ters with M (z=0) 10 15 M ⊙ (Venemans et al 2002;Cucciati et al 2014;Lemaux et al 2014;Lee et al 2014;Diener et al 2015;Bȃdescu et al 2017;Oteo et al 2018;Chanchaiworawit et al 2019).…”
Section: Comparisonmentioning
confidence: 82%
“…whereṄion and the averages in angular brackets are now restricted to that volume instead of to the whole Universe. That is, n is the overdensity (1.67; Chanchaiworawit et al 2019) times the mean cosmic density of hydrogen atoms; α(T ) is the temperaturedependent recombination coefficient to neutral hydrogen, where he typical temperature of the ionised bubble in the overdense volume is equal to that of the whole Universe, calculated as explained in Salvador-Solé et al (2017), times 1.67 2/3 so as to account for the adiabatic contraction produced in the overdensity; C ∼ 3 is the clumping factor (Finkelstein et al 2012; see also Salvador-Solé et al 2017); µ e is the electronic contribution to the mean molecular weight of the cosmic IGM, assuming the usual hydrogenic composition; and a = 0.13 is the cosmic scale factor at z = 6.5. Equation 2 shows how, in order to determine the ionised fraction QII, it is not enough to know the emissivityṄion of the sources in the volume; we also need the rate at which the ionised fraction QII grows.…”
Section: Number Density Of Photons Required To Ionise the Proto-clustermentioning
confidence: 99%